Communication plan for Samsys’ Services: Vencsys & Zapzys - Veríssimo, Filipe Bernardo Teodósio (2022)
The goal of this project, which is to create a communication strategy for Samsys' services, is to create a communication plan for this technology company. To begin, the theoretical foundations for the concepts of "digital marketing," "content marketing," and "social networks" are provided. The communication plan that was produced for the firm in question is then presented in this project. There were certain constraints to this project due to the absence of papers provided by the firm, such as the marketing plan, as well as the lack of essential information offered by Samsys.